2021
DOI: 10.7150/thno.51872
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and molecular aberrations and worse outcome for male patients in systemic mastocytosis

Abstract: In systemic mastocytosis (SM), the clinical features and survival vary greatly. Patient-related factors determining the outcome in SM are largely unknown. Methods: We examined the impact of sex on the clinical features, progression-free survival (PFS), and overall survival (OS) in 3403 patients with mastocytosis collected in the registry of the European Competence Network on Mastocytosis (ECNM). The impact of cytogenetic and molecular genetic aberrations on sex differences was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 32 publications
6
22
1
Order By: Relevance
“…We could confirm in our series that advanced variants of SM are associated with older age and male sex, in line with previous reports [ 27 , 28 ], but their frequency was less than 9% of cases, much lower than reported in the past [ 10 ], and also lower than recently reported in the ECNM registry [ 13 ]. Of interest, the number of new diagnoses of SM-AHN progressively increased from 2006 to 2021, along with a greater experience of the dedicated pathologist, thus confirming that SM-AHN is still an underestimated variant, often diagnosed with a substantial delay [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…We could confirm in our series that advanced variants of SM are associated with older age and male sex, in line with previous reports [ 27 , 28 ], but their frequency was less than 9% of cases, much lower than reported in the past [ 10 ], and also lower than recently reported in the ECNM registry [ 13 ]. Of interest, the number of new diagnoses of SM-AHN progressively increased from 2006 to 2021, along with a greater experience of the dedicated pathologist, thus confirming that SM-AHN is still an underestimated variant, often diagnosed with a substantial delay [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Other, less common (<5%) somatic KIT mutations have also been identified in adult SM patients, including V560G, D815K, D816Y, D816F, D816H, and D820G. Interestingly, the KIT D816V mutation was detected in 84% of men and 75% of women analyzed ( p < 0.001), which is consistent with generally worse outcomes observed for male patients with SM [ 17 ]. Generally, the KIT D816V mutation is less frequently detected in cases of childhood-onset mastocytosis than in adult patients (approximately 40% vs. >80%).…”
Section: Molecular Events In the Development Of Smsupporting
confidence: 66%
“…So far, there are only a few reports of cytogenetic analyses in SM patients. Interestingly, cytogenetic abnormalities are highly restricted to patients with advanced SM in two recent publications [ 17 , 70 ], suggesting that they are unlikely to be primary events in the pathogenesis of SM but rather that these abnormalities promote progression to advanced SM.…”
Section: Molecular Events In the Development Of Smmentioning
confidence: 99%
“…This type of mutation promotes SCF-independent KIT autophosphorylation, which in turn facilitates uncontrolled cellular growth and tumorigenesis [6]. Men were found to be more prone to the KIT D816V mutation and were more likely to acquire advanced forms of SM, translating to worse overall survival (OS) and progression-free survival (PFS) [13]. A small minority of AdvSM cases have also been associated with the V560G, D815K, D816Y, D816F, D816H, and D820G mutations in the KIT gene [14][15][16][17][18][19].…”
Section: Molecular Eventsmentioning
confidence: 99%
“…Longley et al have suggested that KIT mutations affect the regulation of the kinase molecule and alter certain amino acids within the enzymatic domain of the tyrosine kinase [ 20 ]. Although KIT mutations are thought to be crucial in the development of SM, it is postulated that mutations in other genes, such as TET2, SRSF2, RUNX1 and ASXL1, are also required for SM to develop [ 13 , 14 , 21 - 23 ].…”
Section: Reviewmentioning
confidence: 99%